Rhabdomyolysis Induced by Coadministration of Fusidic Acid and Atorvastatin: A Case Report and Comprehensive Review of the Literature - Dimitrios Patoulias; Theodoros Michailidis; Thomas Papatolios; Rafael Papadopoulos; Petros Keryttopoulos (Case Reports in Nephrology)
Statins are among the most widely prescribed medications worldwide. Acute rhabdomyolysis constitutes a potentially life-threatening side effect regardless of whether statins are administered alone or in combination. The potentially fatal combination of a statin and fusidic acid has been well described in the literature. Acute renal failure can be a direct consequence of this drug-drug interaction. We present a case of a 79-year-old woman who presented to our Emergency Department with a one-week history of limb weakness, myalgia, and inability to stand and walk. The patient had been given fusidic acid to treat Methicillin-Sensitive Staphylococcus Aureus (MSSA) positive dermatitis in the 3 weeks prior to admission, while she continued to take her complete therapeutic regimen, which included atorvastatin. Thus, she developed rhabdomyolysis due to the interaction between fusidic acid and atorvastatin. Herein, we report a life-threatening complication of coadministration of fusidic acid and a statin, which is preventable and predictable. The exact mechanism of the interaction is not fully understood, but coadministration of these two medications must be avoided in clinical practice.